A Universal Positioning System for Coupling Characterization of SEM and AFM. (12th August 2021) - Liu, Jinchao; Wang, Andi; Yang, Ji; Yin, Shiheng; Yang, Xianfeng
Abstract : Hyphenated techniques, providing comprehensive information in various aspects such as constituent, structure, functional group, and morphology, play an important role in scientific research. Nowadays, coupling characterization of the same position in microscale is in great need in the field of nanomaterial research and exploration. In this article, a new hyphenated technique was developed to facilitate the coupling characterization of atomic force microscope (AFM) and scanning electron microscope (SEM) by designing a universal positioning system. The system consisted of a specimen holder with coordinate grids and a software for converting the coordinate values of the same point to fit SEM, specimen holder, and AFM system. In working condition, the coordinates of the labeled points and target position were firstly extracted from the SEM operation software, then converted into the numerical values adapted to the specimen holder itself, and finally transformed into the coordinates matching the AFM system. The experimental result showed that a retrieving rate of 96% was achieved for a spherical target with a diameter of 1  μ m in a 30   μ m × 30   μ m square. The hyphenated technique is a universal, accurate, efficient, and financially feasible method in microanalysis field and has great application potential.